2016
DOI: 10.1007/s11295-016-0974-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PaHAP3A stimulates differentiation of ectopic embryos from maturing somatic embryos of Norway spruce

Abstract: Somatic embryogenesis can be used for large-scale propagation of plants. In most conifers, it is only possible to establish embryogenic cultures from zygotic embryos or young seedlings. There is, however, a great interest to propagate selected trees with valuable traits via somatic embryos. To be able to establish embryogenic cultures from adult tissues, more knowledge about the molecular regulation of totipotency and embryogenic potential is needed. In Arabidopsis (Arabidopsis thaliana), LEAFY COTYLEDON1 (LEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Furthermore, when embryogenic cultures of Norway spruce were treated with the HDAC inhibitor trichostatin A (TSA) during maturation, the process was arrested and the expression level of PaHAP3A remained high while the expression of PaVP1 remained low. The development of cotyledonary embryos was not affected when overexpressing PaHAP3A in somatic embryos of Norway spruce, but overexpression stimulated differentiation of ectopic embryos on cotyledonary somatic embryos (Uddenberg et al 2016). In this study, we show that the expression level of a HAP3A-related transcript decreased after stage 1b in both the normal and the abnormal cell lines of Scots pine (Table S7).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Furthermore, when embryogenic cultures of Norway spruce were treated with the HDAC inhibitor trichostatin A (TSA) during maturation, the process was arrested and the expression level of PaHAP3A remained high while the expression of PaVP1 remained low. The development of cotyledonary embryos was not affected when overexpressing PaHAP3A in somatic embryos of Norway spruce, but overexpression stimulated differentiation of ectopic embryos on cotyledonary somatic embryos (Uddenberg et al 2016). In this study, we show that the expression level of a HAP3A-related transcript decreased after stage 1b in both the normal and the abnormal cell lines of Scots pine (Table S7).…”
Section: Discussionmentioning
confidence: 60%
“…T-controls were selected by incubating approximately 100 mg tissue from stage 1 in GUS buffer containing 1 mM 5-bromo-4-chloro-3-indole β-D-glucuronic acid in the darkness at 37°C for up to 5 h (Uddenberg et al 2016). Based on high GUS activity, sub-lines 35S:GUS.1-1, 35S:GUS.1-2, and 35S:GUS.1-3 derived from cell line 61:21, and sub lines 35S:GUS.1-4 and 35S:GUS.1-5 derived from cell line 11:18, were selected.…”
Section: Transgenic Sub Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the Introduction, WUS may be a prime candidate for an RP gene applicable to a wide range of species. Several attempts have been reported for genes other than WUS using BABY BOOM in tobacco (Srinivasan et al 2007), pepper (Heidmann et al 2011) and cacao (Florez et al 2015); LEAFY COTYLEDON 1 (LEC1) and LEC2 in tobacco (Guo et al 2013); LEC1 homolog in conifer (Klimaszewska et al 2010;Uddenberg et al 2016); AGAMOUS-LIKE15 in soybean (Harding et al 2003). However, whether these results are widely applicable to other cultivars or relative species remains unclear and the number of RP genes is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the fact that sweet orange and grapefruit were derived from hybridizations among mandarin and pummelo [43,72,73], we suggest that CsARF19 was originated in mandarin, and has introgression into the hybrids pool. SE initiation is believed to require an induction signal that causes somatic cells to change identity [74]. Previous study showed that two ARF genes (AtARF7 and AtARF19) directly or indirectly target four auxin-responsive LBD (LATERAL ORGAN BOUNDARIES DOMAIN) genes to regulate callus formation in Arabidopsis regeneration [75].…”
Section: Csarf19 Might Be Involved In Citrus Ec Initiationmentioning
confidence: 99%